COMPARISON AMONG THE ALBANIAN AND GREEK OPHIOLITES: IN SEARCH OF CONSTRAINTS FOR THE EVOLUTION OF THE MESOZOIC TETHYS OCEAN - Bortolotti, Valerio; Chiari, Marco; Marcucci, Marta; Marroni, Michele; Pandolfi, Luca; Principi, Gianfranco; Saccani, Emilio (Ofioliti, 2004)
In this paper the stratigraphical, structural, geochemical and petrological features of the Mirdita (Albania) and Pindos, Vourinos, Koziakas, Othrys and Argolis (Greece) ophiolitic nappes are summarised and then compared. These ophiolitic nappes occur as a 700 km long belt running from Albania to Greece. These ophiolitic nappes are located between the west-verging imbricate stack of thrust sheets derived from the Adria plate continental margin to the west and the Pelagonian zone to the east. Each ophiolitic nappe is represented by several end-members represented by the sub-ophiolite mélange, the ophiolite sequence( s) with their sedimentary oceanic cover and the supra-ophiolite deposits. The latter can be divided in syn- and post-emplacement deposits, the first ones are recognised only in Albania. All the described ophiolite sequences are characterised at their base by a well-developed metamorphic sole that represents a further end-member of the ophiolitic nappe. The comparison among the features of all the end-members recognised in the studied ophiolitic nappes allows providing further constraints for the geodynamic reconstructions of the Mesozoic Tethyan oceanic basin located eastwards of the Adria plate.